Women's Colonial Gothic Writing, 1850-1930 Haunted Empire - Edmundson, Melissa (Palgrave Gothic, 2018)
This book explores women writers' involvement with the Gothic. The author sheds new light on women's experience, a viewpoint that remains largely absent from male-authored Colonial Gothic works. The book investigates how women writers appropriated the Gothic genre-and its emphasis on fear, isolation, troubled identity, racial otherness, and sexual deviancy-in order to take these anxieties into the farthest realms of the British Empire. The chapters show how Gothic themes told from a woman's perspective emerge in unique ways when set in the different colonial regions that comprise the scope of this book: Canada, the Caribbean, Africa, India, Australia, and New Zealand. Edmundson argues that women's Colonial Gothic writing tends to be more critical of imperialism, and thereby more subversive, than that of their male counterparts. This book will be of interest to students and academics interested in women's writing, the Gothic, and colonial studies. .